The condition of colonization resistance in surgical patientsearly after the surgery - A. B. Chebotar’; M. V. Choubik; Ye. P. Krasnozhenov; G. Ts. Dambayev (Бюллетень сибирской медицины)
We have examined one of the main components of the mechanism of purulent-inflammation complications in surgical patients. It is normal microflora which reflects the condition of colonization resistance of the organism which is a leading mechanism of opposition to hospital infections. We have established changes of microflora of different biotopes of the organism in dependence on pathologic focus localization and of the period after the surgery. Complex approach to the investigation of colonization resistance allowed to discover not only dysbiotic changes but disturbances of some immunological mechanisms of total and local anti- infectious protection in surgical patients. It is desirable to combine selective decontamination with taking drugs which normalize indigenous micro-flora of the host (special diets, growth stimulators of normal microflora representatives, eubiotics) and immune-stimulating therapy.